Amplitude and phase errors calibration method in satellite-borne dynamic power allocation network - Qi TANG; Jun-min JIANG; Meng XIA (Tongxin xuebao)
For the mobile communication satellite each beam communication traffic distribution was not balanced,leading to differences in transmission power of downlink beam.The implementation architectures of dynamic power allocation network was given,which could allocate the transmitting beam power automatically according to the traffic demand,at the same time ensured the high efficiency of power amplifier.Because the performance of dynamic power allocation network was severely impaired by the mutual coupling among signals when amplitude/phase mismatch was existed,which led to a sharp drop in beam performance.A calibration method for the amplitude and phase errors was proposed.The decoupling of calibration signal was realized by using the cross-correlation orthogonal characteristic of the orthogonal zero-correlation zone (ZCZ) sequences in the zero correlation interval,and communication was free from calibration by reducing the transmit power for the excellent self-correlation characteristic of the ZCZ sequences.Performance simulation and far field test show that under the condition that the calibration signal power is less than the normal signal 10 dB,the amplitude error is less than 0.1 dB,the phase error is less than 0.3°,and the gain loss within the main lobe is less than 0.2 dB after calibration.